Fatigue characterization and modeling of AZ31B magnesium alloy spot-welds - Behravesh, Seyed Behzad; Jahed, Hamid; Lambert, Steve (Elsevier, 2014)
Cyclic behavior of AZ31B spot-welds was studied using different specimen configurations, and compared with steel and aluminum spot-welds. Fatigue strength of magnesium spot-welds was similar to aluminum and less than steel. Three failure modes were observed in tensile-shear specimens and one mode of failure in cross-tension specimens. Fatigue crack initiation life was 50% and 30% of the total life for tensile-shear and cross-tension specimens, respectively. A number of available fatigue models were assessed by predicting fatigue life of magnesium spot-welds. Although these models do not account for the asymmetric cyclic hardening behavior, some of them performed successfully for magnesium spot-welds. (C) 2014 Elsevier Ltd. All rights reserved.
The final publication is available at Elsevier via http://dx.doi.org/10.1016/j.ijfatigue.2014.01.026 © 2014. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: Magnesium; Spot weld; Characterization; Fatigue modeling